Durabilidade das soluções e estratégias de manutenção de fachadas de edifícios - I. FLORES-COLEN (2003)
The purpose of this paper is to reflect upon a set of fundamental aspects to implement maintenance strategies, from the design stage to the carrying out of the inspection and maintenance actions in current buildings façades. Correlation matrixes between the various parameters (requirements, performance levels, durability criteria, maintenance type and costs) are exemplified. The development of theses matrixes, in the future, aims at contributing to the systemization of the technical data used in façades, inorder to facilitate the definition of quality criteria, the choice of façade solutions and the maintenance planning, with optimization of the global costs.Keywords: Requirements, Durability, Façades, Maintenance, Buildings